Former Yugoslav Republic of Macedonia : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2004)
This Report on the Observance of Standards and Codes on Data Module on the Former Yugoslav Republic of Macedonia reviews assessment by agency and dataset. The mission has a set of recommendations for Macedonia's statistical practices, on discussions with the data-producing agencies and on responses from data users. They are designed to increase further FYR Macedonia's adherence to internationally accepted statistical practices and would, in the mission's view, enhance the analytical usefulness of FYR Macedonia's statistics.